2015
DOI: 10.5350/semb.20150430023217
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Aspiration Syndrome (MAS)

Abstract: Derleme / Review ÖZET:Mekonyum Aspirasyon Sendromu (MAS) Mekonyum aspirasyonu, tipik olarak fetal hipoksik iskemik stresin intestinal peristaltizme yol açarak, amniyotik sıvının mekonyum ile kontaminasyonu ve gasping sonucu akciğerin derin dokularına kadar nüfuz etmesi ile ortaya çıkar. Tüm doğumların %10-15'inde amniyotik sıvı mekonyum ile kontamine iken bu bebeklerin %5-10'unda mekonyum aspirasyonu ve solunum yetersizliği gelişir. Bu derlemede, MAS klinik bulguları, tanısal ve tedavisel yaklaşımı ile ilgili … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…PPHT has been reported at a rate of 6-25% in newborns with HIE who were enrolled in clinical studies of head and whole-body cooling, which is higher than the rate in the general population. [ 11 , 12 ] Shankaran et al [ 13 ] , who investigated the relationship between the degree of hypothermia and PPHT, demonstrated that when patients were cooled to 33.5 and 32 o C for 72 or 120 hours, the need for iNO and extracorporeal membrane oxygenation (ECMO) increased in the group cooled to 32 o C. They also demonstrated that the mild hypothermia used in HIE treatment was not associated with PPHT. Six of our patients (four with MAS and two with IUGR) received therapeutic hypothermia for HIE, and their body temperatures were maintained within the range of 33.5-34.5 o C.…”
Section: Discussionmentioning
confidence: 99%
“…PPHT has been reported at a rate of 6-25% in newborns with HIE who were enrolled in clinical studies of head and whole-body cooling, which is higher than the rate in the general population. [ 11 , 12 ] Shankaran et al [ 13 ] , who investigated the relationship between the degree of hypothermia and PPHT, demonstrated that when patients were cooled to 33.5 and 32 o C for 72 or 120 hours, the need for iNO and extracorporeal membrane oxygenation (ECMO) increased in the group cooled to 32 o C. They also demonstrated that the mild hypothermia used in HIE treatment was not associated with PPHT. Six of our patients (four with MAS and two with IUGR) received therapeutic hypothermia for HIE, and their body temperatures were maintained within the range of 33.5-34.5 o C.…”
Section: Discussionmentioning
confidence: 99%
“…The European Research Journal 2019;5 (5):776-780 iagnosis of meconium aspiration syndrome (MAS) is made by the presence of respiratory distress and other characteristic radiologic findings in babies born with meconium-stained amniotic fluid (MSAF) [1, 2,]. In the healthy newborn, the first meconium outflow is between 24 th and 48 th hours and it is rarely seen between 20 and 34 weeks of pregnancy [1,2].…”
mentioning
confidence: 99%
“…Meconium causes harm in lungs with various mechanisms and that was defined as MAS by the presence of respiratory distress and other characteristic radiologic findings in babies born with MSAF [2,5]. The clinical picture may vary from mild respiratory distress to severe respiratory failure.…”
mentioning
confidence: 99%